INFLUENCE COMPENSATION, WORKLOAD AND JOB SATISFACTION TO TURNOVER INTENTION - Muhammad Arkan Raihan; Chaerudin Chaerudin (Dinasti Publisher, 2021)
This study aims to test and analyze the effect of compensation, workload and job satisfaction on employee turnover intentions at PT. XYZ Research data is data collected from interviews, questionnaires and supporting data from PT. XYZ for 3 consecutive years from 2017 to 2019. The sampling method used is the saturation sampling method. From a population of 125 people, the sample used was 95 people as well. The analytical method used in this study is multiple linear regression analysis. The results showed compensation, workload and job satisfaction together (simultaneously) significantly influence turnover intention. Partially shows that compensation has a negative and significant effect on turnover intention. Workload has a negative and significant effect on turnover intentions. Job satisfaction has a negative and significant effect on turnover intentions.